Brain Somatic Variant in Ras-Like Small GTPase RALA Causes Focal Cortical Dysplasia Type II - Xu, Han; Gao, Kai; Liu, Qingzhu; Wang, Tianshuang; Zhang, Zhongbin; Cai, Lixin; Wu, Ye; Jiang, Yuwu (Frontiers in Behavioral Neuroscience, 2022)
Purpose: In our group's previous study, we identified the first somatic variant of RALA c.G482A that encodes a small GTPase of the Ras superfamily in the postoperative brain tissue from an epilepsy patient with focal cortical dysplasia type II (FCD II) using deep whole-exome sequencing and targeted amplicon sequencing. To date, the role of RALA in brain development is not yet known. Here, we report that the RALA somatic variant led to FCD type II through activation of the mTOR pathways. Methods: HEK293T cells were transfected in vitro to analyze the expression of the RalA protein, as well as phosphorylated S6 (P-S6), one of the major markers of mTOR pathway activation, RalA GTPase activity, and the interaction between RalA and its downstream binding effectors. In vivo, wild-type, and mutant RALA plasmids were transfected into the local cortex of mice using in utero electroporation to evaluate the effect of RALA c.G482A on neuronal migration. Results: The RALA c.G482A mutation increased RalA protein expression, the abnormal activation of the mTOR pathways, RalA GTPase activity, and binding to downstream effectors. RALA c.G482A local transfection in the embryonic brain in utero induced abnormal cortical neuron migration in mice. Conclusions: This study demonstrated for the first time that the somatic gain-of-function variant of RALA activates the mTOR pathway and leads to neuronal migration disorders in the brain, facilitating the development of FCD II. Therefore, RALA brain somatic mutation may be one of the pathogenic mechanisms leading to FCD II that is always related to drug-resistant epilepsy in children. However, more somatic variations of this gene are required to be confirmed in more FCD II patient brain samples.